Migrants’ Remittances from the United Kingdom : International Remittances and Access to Financial Services for Migrants in London, UK, A Greenback 2.0 Report - World Bank (World Bank, Washington, DC, 2015)
This report will share key findings from the research, starting with an overview in section two of the international remittance context and the UK remittance market. It also provides a view on trends in the UK market, particularly in the wake of significant bank de-risking, leading many remittance service providers (RSPs) to seek out alternative banking solutions. Section three outlines the objectives of the research, the survey design and the sampling techniques for the fieldwork. This is followed by Section 4, which presents the empirical findings of the 602 interviews collected. It begins with demographic and economic characteristics of the participants before focusing on migrants’ attitudes and behaviors regarding remittance sending, using financial services, and savings and investment. Given the current environment for remittance service providers in the UK (and in several other countries) and the global commitment to reducing remittance costs, there is a focus on the service providers used and the costs incurred. Finally, the report concludes with a summary of the main findings and provides recommendations on addressing the barriers and issues faced by migrants in London regarding financial and remittance services, as well as potential areas of further inquiry.